2005
DOI: 10.3201/eid1107.041273
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Recombination in ORF1/ORF2 Overlap

Abstract: Norovirus (NoV) genogroups I and II (GI and GII) are now recognized as the predominant worldwide cause of outbreaks of acute gastroenteritis in humans. Three recombinant NoV GII isolates were identified and characterized, 2 of which are unrelated to any previously published recombinant NoV. Using data from the current study, published sequences, database searches, and molecular techniques, we identified 23 recombinant NoV GII and 1 recombinant NoV GI isolates. Analysis of the genetic relationships among the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
244
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(262 citation statements)
references
References 36 publications
16
244
0
2
Order By: Relevance
“…In addition, the high prevalence of FCV in such colonies provides an ideal environment for mixed infections. As a result recombination events between strains, similar to those reported for other caliciviruses [7,46,50,73], have been identified in such colonies, and provide a further mechanism for the diversification of viruses [16]. Whether these evolutionary events are associated with the selection of more virulent, faster replicating viral variants remains to be determined.…”
Section: Fcv-associated Virulent Systemic Diseasementioning
confidence: 78%
“…In addition, the high prevalence of FCV in such colonies provides an ideal environment for mixed infections. As a result recombination events between strains, similar to those reported for other caliciviruses [7,46,50,73], have been identified in such colonies, and provide a further mechanism for the diversification of viruses [16]. Whether these evolutionary events are associated with the selection of more virulent, faster replicating viral variants remains to be determined.…”
Section: Fcv-associated Virulent Systemic Diseasementioning
confidence: 78%
“…ORF1 encodes nonstructural proteins, while ORF2 and ORF3 encode the structural proteins VP1 and VP2, respectively. Recombination at the ORF1-ORF2 junction has been reported (12). Amino acid substitutions in the P2 domain, located within the VP1 of NoVs, have also been reported, especially in NoV GII.4 (13).…”
Section: Introductionmentioning
confidence: 99%
“…While Lindesmith and coworkers have identified a recombination breakpoint at residue 265 located near the P1-1/P2 domain interface of NoV GII.4 strains (Lindesmith et al, 2008), this recombination break point was not found in this study. The absence of detected recombinants might be due to the fact that we did not have access to ORF1/ORF2 overlap sequences, previously found associated with NoV recombination break points (Bull et al, 2005(Bull et al, , 2007Phan et al, 2007). Thus, we cannot rule out that recombination occurred at the ORF1/ORF2 junction.…”
mentioning
confidence: 96%
“…Since RNA recombination is believed to be one of the major driving forces in viral evolution (Worobey & Holmes, 1999), including NoV (Bull et al, 2005(Bull et al, , 2007Phan et al, 2007), we searched the 134 full-length (P1-1 and P2 capsid domains) NoV capsid nudeotide sequences for recombination events. The sequences were first aligned using CLUSTAL W-multialign with default settings on the Mobyle portal (Pasteur Institute), and then analysed by the RDP2 software to search for possible recombinants using different conventional recombination detection methods such as GENECONV, SIMPLOT, BOOTSCAN, MAXIMUM x 2 and CHIMAERA (Martin et al, 2005).…”
Section: No Recombination Detected Within the P1-1 And P2 Capsid Domainsmentioning
confidence: 99%
See 1 more Smart Citation